2012
DOI: 10.1002/pssc.201200673
|View full text |Cite
|
Sign up to set email alerts
|

EPR and ODMR defect control in AlN bulk crystals

Abstract: The results of pulse electron paramagnetic resonance (EPR), electron nuclear double resonance (ENDOR) and optically detected magnetic resonance (ODMR) are presented to show the electron structure of deep level defect color center in AlN single crystals such as a nitrogen vacancy in neutral charge state (VN0) as well as a new type of point defect such as exchange–coupled pair of the nitrogen vacancies (VN‐VN). Analyzing spin density distribution of an unpaired VN0 electron on different ions of AlN crystalline l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(14 reference statements)
0
4
0
1
Order By: Relevance
“…These findings indicate that the S = 3/2 state of V N 2− might be of potential interest as a defect qubit, but it might be difficult to realize, as highly n- doped w- AlN is difficult to obtain 47 48 . Interestingly, the V N 0 S = 1/2 state has been recently detected using electron paramagnetic resonance 18 19 . Based on these results, we considered the Fermi level range in the vicinity of the stability region of V N 0 , which might be accessible in experiments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings indicate that the S = 3/2 state of V N 2− might be of potential interest as a defect qubit, but it might be difficult to realize, as highly n- doped w- AlN is difficult to obtain 47 48 . Interestingly, the V N 0 S = 1/2 state has been recently detected using electron paramagnetic resonance 18 19 . Based on these results, we considered the Fermi level range in the vicinity of the stability region of V N 0 , which might be accessible in experiments.…”
Section: Resultsmentioning
confidence: 99%
“…We found that negatively charged nitrogen vacancies exhibit localized spin-triplet states in n- type aluminum nitride under realistic strain conditions. Nitrogen vacancies are naturally incorporated in aluminum nitride during crystal growth and they are known to be the main source of the intrinsic n- type behavior of aluminum nitride 18 19 20 21 , thus making the nitrogen vacancy spins easily amenable to experimental investigations 18 19 . Extra n- type doping control might be achievable by introducing substitutional oxygen impurities (O N ) during crystal growth 24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Первоначально этот метод использовался для выращивания кристаллов SiC [1], а позднее был успешно применен и для А1N [2]. Высокое качество получаемых этим методом кристаллов А1N было подтверждено их микроскопическими, оптическими, рентгеновскими исследованиями [2], а также изучением электронного парамагнитного резонанса [3]. Позднее удалось дополнительно повысить качество выращиваемых кристаллов за счет испарения затравки непосредственно в ходе процесса роста, что позволило избежать их растрескивания и образования микротрещин в результате процесса послеростового остывания [4].…”
Section: Introductionunclassified